Speed of sound data, derived perfect-gas heat capacities, and acoustic virial coefficients of a calibration standard natural gas mixture and a low-calorific H2-enriched mixture. (July 2021) - Lozano-Martín, Daniel; Vega-Maza, David; Moreau, Alejandro; Martín, M. Carmen; Tuma, Dirk; Segovia, José J.
Highlights: Comparison between a 11 component synthetic natural gas mixture and a H2 -enriched blend is reported. A spherical acoustic resonator provides accurate speed of sound data. Heat capacities and virial coefficients are derived from experimental speeds of sound. Performance of reference equations of state such as GERG 2008 and AGA8 is discussed. Abstract: This work aims to address the technical aspects related to the thermodynamic characterization of natural gas mixtures blended with hydrogen for the introduction of alternative energy sources within the Power-to-Gas framework. For that purpose, new experimental speed of sound data are presented in the pressure range between (0.1 up to 13) MPa and at temperatures of (260, 273.16, 300, 325, and 350) K for two mixtures qualified as primary calibration standards: a 11 component synthetic natural gas mixture (11 M), and another low-calorific H2 -enriched natural gas mixture with a nominal molar percentage x H 2 = 3 % . Measurements have been gathered using a spherical acoustic resonator with an experimental expanded ( k  = 2) uncertainty better than 200 parts in 10 6 (0.02%) in the speed of sound. The heat capacity ratio as perfect-gas γ pg, the molar heat capacity as perfect-gas Cp, m pg, and the second β a and third γ a acoustic virial coefficients are derived from the speed of sound values. All the results are compared with the reference mixture models for natural gas-like mixtures, the AGA8-DC92 EoS and the GERG-2008 EoS, with special attention to the impact of hydrogen on those properties. Data are found to be mostly consistent within the model uncertainty in the 11 M synthetic mixture as expected, but for the hydrogen-enriched mixture in the limit of the model uncertainty at the highest measuring pressures.